IEM – ICE joint conference on 'Future Engineers 2017 Malaysia - Inspiring the Workforce of Tomorrow' - Ooi, Teik Aun, Ir. Dr (The Institution of Engineers, Malaysia (IEM), 2019)
Link to publisher’s homepage at https://www.myiem.org.my/